Classification and Management of Failed Fixation of the Volar Marginal Fragment in Distal Radius Fractures - Orbay, M. Carolina; Orbay, Jorge L. (Journal of Wrist Surgery, 2021)
Greater understanding of specific fracture patterns following distal radius fractures has arisen with the advent of volar plating. The volar marginal fragment (VMF) is a small peripheral piece of bone which is critical to carpal stability. Failure to achieve good fixation of the VMF can result in volar subluxation of the carpus and distal radioulnar joint instability. Due to its small, distal nature, this fragment can be easily missed and difficult to fix. Loss of reduction of the VMF following operative fixation presents specific challenges and surgical considerations dictated by patient characteristics and timing. Our goal of this review is to present a classification system for these failed VMFs which can help guide surgical treatment as well as expected outcomes.
Keywords: distal radius fractures; hook plate; revision distal radius; volar lunate facet; volar marginal fragment